Effects of Lecithin Supplementation in Feed of Different fat Levels on Serum Indexes and Liver Health of Laying Hens - Hu, Gui-Li; Xiong, Juan; Liu, Yang; Yang, Hong-Jun; Hu, Ling-Ling; Chen, Peng; Wang, Xin; Liao, Shuang; Lv, Tuo; Liu, Chun-Jie; Huang, Peng; Lin, Qian (Frontiers in Physiology, 2022)
The aim of this experiment was to investigate the effect of lecithin on serum-related indicators and liver health in laying hens under the influence of high-fat diets. 180 peak laying hens at 40 weeks of age were randomly assigned to one of the four diets using a 2×2 factorial and fed for 5 weeks. The results showed that compared to the low-fat group, the high-fat group had significantly lower egg production (P < 0.05) and higher average daily feed intake and feed-to-egg ratio (P < 0.05). At 21 days, the serum levels of TC and SOD were significantly higher (P < 0.05), HDLC levels were significantly lower (P < 0.01), CAT activity was significantly lower (P < 0.05), TG and MDA levels in liver were significantly higher (P < 0.01) and SOD activity in liver was significantly lower (P < 0.05) in layers supplemented with lecithin. CAT activity in serum was significantly increased (P < 0.01) and T-AOC activity in liver was significantly decreased (P < 0.05) after increasing the dietary fat concentration. The addition of lecithin and the increase in dietary fat concentration had a highly significant interaction on serum CAT activity and liver TG content in layers (P < 0.01). At 35 days, the serum ALT activity was significantly higher (P < 0.01), serum GSH-Px and CAT activity were significantly higher (P < 0.05), and serum TC content and T-AOC activity were significantly lower (P < 0.05) in layers supplemented with lecithin. Increasing dietary fat concentration significantly decreased ALT, AST and GSH-Px activity in serum (P < 0.05), significantly increased TG and MDA content in liver (P < 0.05), and highly significantly decreased SOD content in liver (P < 0.01) in layers. The addition of lecithin and increasing dietary fat concentration had a highly significant reciprocal effect on serum ALT viability and CAT viability (P < 0.01) and liver TG and MDA content and SOD viability (P < 0.05) in layers. In conclusion, the addition of lecithin to high-fat diets reduced the fat content in the liver of layers and improved the antioxidant capacity of the liver